Comparison of cardiac MRI with PET for assessment of myocardial viability in patients with coronary chronic total occlusion. Issue 5 (May 2019) - Li, J.N.; He, Y.; Dong, W.; Zhang, L.J.; Mi, H.Z.; Zhang, D.F.; Huang, R.C.; Song, X.T.
Abstract : AIM: To compare cardiac magnetic resonance imaging (MRI) and positron-emission tomography (PET) assessment of myocardial viability in patients with coronary chronic total occlusion (CTO). MATERIALS AND METHODS: Eighty patients with coronary CTO underwent cardiac MRI and PET. Cardiac MRI images were analysed using a 17-segment model, and late gadolinium enhancement (LGE) and wall motion were scored. PET was used to classify myocardial viability via myocardial perfusion and 18F-fluorodeoxyglucose, digital superscript uptake. RESULTS: With PET as the reference standard, the sensitivity of cardiac MRI in detecting myocardial viability was 95.3%, specificity was 87.5%, positive predictive value was 96.8%, negative predictive value was 84.2%, and accuracy was 93.8% on a per patient basis. The receiver operator characteristic curve was used to analyse the performance of cardiac MRI in the detection of myocardial viability on a per-patient basis and the area under the curve was 0.910 (95% confidence interval 0.805 to 1). Cardiac MRI had the highest sensitivity and specificity for differentiating viable and non-viable myocardium as defined by PET when the cut-off value of LGE was 50%. The motion consistency and correlation of cardiac MRI and PET were analysed and kappa was 0.788 ( r= 0.825; p< 0.001). CONCLUSION: Compared with PET, cardiac MRI assessment of myocardial viability in patients with coronary CTO has high sensitivity, specificity, and accuracy. Therefore, cardiac MRI can be used as an important method for evaluating myocardial viability in coronary CTO patients. Highlights: There is little study on the value of cardiac MRI analysis of myocardial viability in patients with coronary CTO. Cardiac MRI assessment of myocardial viability in patients with coronary CTO has good sensitivity and specificity compared to PET. Cardiac MRI can be used as an important method for evaluating myocardial viability in patients with coronary CTO.